Pelatihan Pembuatan Stick Pisang Ibu-ibu Kelompok Jalapagos Desa Buon Mandiri Kecamatan Luwuk Utara - Ramadhani Chaniago; Haruni Ode; Rahman Dani Lasamadi; Darni Lamusu (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
compared to other fruits. Bananas have a variety of nutritional content and are needed by the body. Bananas also have the potential to be processed into various kinds of preparations such as chips, pastries, cakes and sticks. Sticks are snacks or light snacks that are loved by many people from children to adults. This activity is divided into three sessions, namely a material delivery session, a practice session, and a question and answer session. After the implementation of training activities on making banana sticks, it can increase the knowledge and skills of mothers in Buon Mandiri Village, North Luwuk District, Banggai Regency about the potential of banana plants and can provide an increase in the economic value of the family